Evaluation of Hepatoprotective and Gastroprotective Activities of Paspalidium flavidum Leaves Extract in Experimental Animal Models: Hepato- and gastroprotective effect of Paspalidium flavidum - Ismail, Sana; Naveed Mushtaq, Muhammad; Shabbir, Ushna; Saima,; Razzaq, Asma; Ramzan, Hafiz Muhammad; Shoukat, Alina; Ahsan, Haseeb; Movafagh, Abolfazl; Kahrizi, Danial; Anjum, Irfan (Cellular and Molecular Biology, 2022)
Paspalidium flavidum (watercrown grass), a medicinal plant, is traditionally used in liver ailments and stomach problems. The hepatoprotective and gastroprotective activities of the aqueous methanol extract of Paspalidium flavidum (AMEPF) were studied in experimental animal models. Paracetamol and aspirin were used to induce hepatotoxicity and gastric ulcer in rats, respectively. Biochemical hepatic parameters, gastric pH, total acidity, ulcer index, percentage protection, nitric oxide and TNF-α were measured in AMEPF-treated groups. Moreover, GC-MS analysis of AMEPF was performed. Pretreatment with AMEPF improved the blood lipid profile and restored liver function tests in paracetamol-induced hepatotoxicity. While in aspirin-induced gastric ulcer, oral administration of AMEPF significantly reduced (P<0.05) the gastric lesions, total acidity and ulcer scoring index, TNF-α with upregulation of nitric oxide when compared with the Diseased group. AMEPF exhibited anti-lipid peroxidation activity. Histopathological studies were in good agreement with the biochemical findings. GC-MS analysis revealed the presence of anti-oxidant phyto-constituents, including oleic acid and 1,2-benzenedicarboxylic acid, mono(2-ethylhexyl) in AMEPF. This study suggested that aqueous methanol extract from the leaves of P. flavidum has beneficial hepatoprotective and gastroprotective activities related to its anti-oxidant phytochemicals.